2021
DOI: 10.5194/hess-2021-202
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards disentangling heterogeneous soil moisture patterns in Cosmic-Ray Neutron Sensor footprints

Abstract: Abstract. Cosmic-Ray Neutron Sensing (CRNS) allows for non-invasive soil moisture measurements at the field scale. The derivation of soil moisture generally relies on secondary cosmic-ray neutrons in the epithermal-to-fast energy range. Most approaches and processing techniques for observed neutron intensities are based on the assumption of homogeneous site conditions within the measurement footprint of the neutron detector. In this study we investigated how a non-uniform soil moisture distribution within the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…However, some have identified the need for additionally calibrating the ai parameters to reproduce site-specific SWC dynamics or match local conditions (e.g. Iwema et al, 2015;Rasche et al, 2021;Rivera Villarreyes et al, 2011).…”
Section: Synthetic Soil Water Content Timeseries For Each Slu Unit (S...mentioning
confidence: 99%
“…However, some have identified the need for additionally calibrating the ai parameters to reproduce site-specific SWC dynamics or match local conditions (e.g. Iwema et al, 2015;Rasche et al, 2021;Rivera Villarreyes et al, 2011).…”
Section: Synthetic Soil Water Content Timeseries For Each Slu Unit (S...mentioning
confidence: 99%
“…A4). An example is the CRNS station at the Fuerstensee site in Germany (Rasche et al, 2021). The footprint represented by the CRNS measurement at this site includes a sand lens in the center of the footprint, which is surrounded by peat soils.…”
Section: How Representative and Accessible Is The Soil Moisture Data?mentioning
confidence: 99%
“…Such investigations are particularly important given that the intensity of thermal neutrons also depends on soil moisture content and soil chemistry, since thermal neutrons are particularly strongly absorbed by certain elements in the soil (Andreasen et al., 2016; Zreda et al., 2008). In addition, recent studies have shown that the sensing volume of thermal neutrons is much smaller than in the case of epithermal neutrons (Bogena et al., 2020; Rasche et al., 2021). Using neutron transport simulations, it was found that thermal neutrons have a radial footprint of approximately 45 m, which increases only slightly with soil moisture content, and a sensing depth that increases from 10 to 65 cm with decreasing soil moisture content from 0.50 to 0.01 m 3 /m 3 (Jakobi et al., 2021).…”
Section: Introductionmentioning
confidence: 99%